Peningkatan Hasil Belajar Peserta Didik melalui Pendekatan Pembelajaran Berdiferensiasi berbasis LKPD pada Materi IPAS di Kelas V SDN Besuk 1 - Indri Nur Aliffia; Dian Aliffatul Inayah; Rian Damariswara; Yeny Shirot Pudji Lestari (Jurnal Simki Postgraduate, 2024)
Classroom Action Research with the title "Improving Student Learning Outcomes Through Differentiated Learning Approach Based on Student Worksheets on Science Material in Class V SDN Besuk 1" which has been written by Dian Aliffatul Inayah and Indri Nur Aliffia, PPG students of Nusantara PGRI University Kediri This research is motivated by the low learning outcomes of students in the science subject below the KKM, which is 75. Other factors that cause this are learning that is still centered on the teacher and the teacher has not used a learning model that is in accordance with the needs of students, so we want to research "How Differentiated Learning Can Improve Learning Outcomes in Natural and Social Sciences (IPAS) in Class V Students of SDN Besuk 1, Gurah District, Kediri Regency in the 2024/2025 Academic Year?" with a descriptive quantitative approach. So after conducting the research, the results showed that in the pre-cycle phase, the results of student completion were only 40% of the total number of class V. In cycle 1, student learning outcomes increased to 60% so that it was continued to cycle II where at this stage there was an indication of an increase in learning outcomes to 88%. Based on these data, it can be concluded that student learning outcomes in cycle II were declared to meet the graduation standards so that the research phase was stopped.